2014
DOI: 10.1038/aps.2014.74
|View full text |Cite
|
Sign up to set email alerts
|

Telekin suppresses human hepatocellular carcinoma cells in vitro by inducing G2/M phase arrest via the p38 MAPK signaling pathway

Abstract: Aim: Telekin, isolated from the Chinese herb Carpesium divaricatum, has shown anti-proliferation effects against various cancer cells, including hepatocellular carcinoma cells. In this study, we investigated the anti-proliferation mechanisms of telekin in human hepatocellular carcinoma HepG2 cells in vitro. Methods: HepG2 cells were treated with telekin. Cell viability was evaluated using MTT assay. Flow cytometry was used to measure cell cycle profiles, ROS level and apoptosis. The protein expression levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…These results reveal that miR‐101 probably contributes to the tumorigenesis and metastasis of HCC. Previous studies have reported the role of these pathways in liver cancer . The GO term analysis indicated that these potential target genes of miR‐101‐3p/5p were significantly involved in the regulation of the cell cycle and cell proliferation, which are associated with tumor occurrence or stepwise development.…”
Section: Discussionmentioning
confidence: 95%
“…These results reveal that miR‐101 probably contributes to the tumorigenesis and metastasis of HCC. Previous studies have reported the role of these pathways in liver cancer . The GO term analysis indicated that these potential target genes of miR‐101‐3p/5p were significantly involved in the regulation of the cell cycle and cell proliferation, which are associated with tumor occurrence or stepwise development.…”
Section: Discussionmentioning
confidence: 95%
“…CDKs usually interact with cyclin proteins to perform their functions in regulating the cell cycle. In particular, the Cdc2/Cyclin B1 complexes are recognized as the M-phase-related protein in eukaryotic cells [22]. Actinomycin V induced phosphor-Cdc2 but reduced Cyclin B1 and Cdc2 expressions, thereby leading to cell cycle arrest in G2 phase without entering the M phase.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that telekin at 2.5–10 µmol/L could significantly inhibit the cell proliferation by inducing cellular apoptosis via decreasing the expressions of Bcl-2 and Apaf-1, increasing the expression of Bax, releasing Cyt-c, and activating caspases-9 and -3 in liver cancer HepG2 cells (Zheng B. et al, 2013). Additional studies also showed that Telekin displayed potent cytotoxicity and induced apoptosis against multiple cancer cells (Li et al, 2014; Wang X. et al, 2015). The chemical structures of active compounds from anticancer TCMs that affect Bcl-2/Bax signaling pathway are illustrated in Figure 3 .…”
Section: Anticancer Tcms Through Affecting the Bcl-2/bax Pathwaymentioning
confidence: 92%